2013
DOI: 10.1186/1756-0500-6-353
|View full text |Cite
|
Sign up to set email alerts
|

Orbital positron emission tomography/computed tomography (PET/CT) imaging findings in graves ophthalmopathy

Abstract: BackgroundWe aimed to describe orbital positron emission tomography/computed tomography (PET/CT) imaging findings, both structural and metabolic, in different clinical stages of Graves ophthalmopathy (GO). This prospective, observational, cross-sectional study examined 32 eyes of 16 patients with GO.MethodsPatients were assessed with a complete ophthalmological evaluation and assigned a VISA classification for GO. All patients underwent serum thyroid hormone measurement, antibody profile, and 18-fluorodeoxyglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…The lack of correlation between SUVmax and severity of GO is in line with prior publications on this topic: García-Rojas et al analyzed the 18 F-FDG-PET/CT scans of 16 patients with GO and found that FDG uptake in the EOM as assessed by SUVmax was significantly higher than in the non-affected control group [22]. However, a subsequent study by the same group did not find any correlation between SUVmax on the one hand and muscle thickness and clinical inflammation score on the other hand [33]. Similarly, a study by Uslu-Beşli et al showed that 18 F-FDG uptake as assessed by SUVmax was elevated in patients with GO when compared to a nonaffected control group but they as well did not find a correlation between SUVmax and muscle thickness [34].…”
Section: Differences In Pet Parameters Among Severity-stratified Groupssupporting
confidence: 86%
“…The lack of correlation between SUVmax and severity of GO is in line with prior publications on this topic: García-Rojas et al analyzed the 18 F-FDG-PET/CT scans of 16 patients with GO and found that FDG uptake in the EOM as assessed by SUVmax was significantly higher than in the non-affected control group [22]. However, a subsequent study by the same group did not find any correlation between SUVmax on the one hand and muscle thickness and clinical inflammation score on the other hand [33]. Similarly, a study by Uslu-Beşli et al showed that 18 F-FDG uptake as assessed by SUVmax was elevated in patients with GO when compared to a nonaffected control group but they as well did not find a correlation between SUVmax and muscle thickness [34].…”
Section: Differences In Pet Parameters Among Severity-stratified Groupssupporting
confidence: 86%
“…are used in ophthalmology and other applications [89]. The non-invasive imaging and optical modalities such as bioluminescence, reflectance, magnetic resonance spectroscopy imaging (MRSI), positron emission tomography (PET), and contrast-enhanced perfusion MRI have their intrinsic limitations for the investigation of ocular and tumor-related neovascularization [90][91][92][93][94][95]. The human eye, by nature, promotes the sub-cellular mediated resolution and non-invasive in vivo imaging of the retina and its vascularization in healthy and diseased states (retinal tumor, DR, uveitis, etc.).…”
Section: Imaging Biomarkersmentioning
confidence: 99%
“…This modality has not been widely used in the field of clinical ophthalmology to date [25], although its use is promising for the diagnosis of primary ocular tumours and for neurophysiologic studies [26,27,28,29,30]. In recent years, it has emerged in the research field as an essential tool for the study of the pharmacokinetics of different ophthalmic formulations, since it provides images of the drug’s biodistribution and/or its effect on the eye.…”
Section: Positron Emission Tomographymentioning
confidence: 99%